Chronic cough: Investigations, management, current and future treatments. Issue 6 (2nd November 2021) - Satia, I.; Wahab, M.; Kum, E.; Kim, H.; Lin, P.; Kaplan, A.; Hernandez, P.; Bourbeau, J.; Boulet, L. P.; Field, S. K.
Abstract: Chronic cough, defined as cough lasting 8 weeks or longer, is a condition for which there is currently no licensed treatment. Chronic cough affects approximately 16% of Canadian adults between the age of 45 and 85 years and is often associated with physical, social, and psychological impairments. The purpose of this state-of-the-art review is to highlight the investigations, management, current and future treatment options and mechanistic concepts underlying chronic cough. Assessments of chronic cough should include a detailed history and examination to identify potential causes and triggers. Conditions associated with chronic cough include ACE inhibitor use, smoking, asthma, non-asthmatic eosinophilic bronchitis, gastroesophageal reflux disease, and upper airways cough syndrome. The impact and severity of chronic cough can be assessed in clinic using subjective questionnaires. Persistent cough despite optimal treatment of the underlying condition is called refractory chronic cough (RCC). Persistent cough for which no underlying cause is found, is labeled unexplained chronic cough (UCC). If treatment of underlying disease is unsuccessful at controlling cough despite adequate duration and adherence to the treatment, neuromodulator treatments such as speech and language therapy and/or low dose opioid, gabapentin, and pregabalin may be therapeutic options. There is no licensed treatment for RCC/UCC but a new class of medication targeting the purinergic P2X3 receptor is currently under consideration for regulatory approval with other P2X3 antagonists in phase 2 and phase 3 clinical development. Approval of this new treatment class may represent a hopeful advancement for patients suffering with chronic cough. RÉSUMÉ La toux chronique, définie comme une toux qui dure huit semaines ou plus, est une affection pour laquelle il n'existe actuellement aucun traitement autorisé. La toux chronique affecte environ 16 % des adultes canadiens âgés de 45 à 85 ans et est souvent associée à des déficiences physiques, sociales et psychologiques. Le but de cette revue de l'état de l'art est de mettre en évidence les investigations, la prise en charge, les options de traitement actuelles et futures et les concepts mécanistes sous-jacents à la toux chronique. Les évaluations de la toux chronique devraient inclure un historique détaillé et un examen pour déterminer les causes et les déclencheurs potentiels. Les affections associées à la toux chronique comprennent l'utilisation d'inhibiteurs de l'ECA, le tabagisme, l'asthme, la bronchite éosinophile non asthmatique, le reflux gastro-oesophagien et le syndrome de toux des voies respiratoires supérieures. L'impact et la gravité de la toux chronique peuvent être évalués en clinique à l'aide de questionnaires subjectifs. Une toux persistante malgré un traitement optimal de l'affection sous-jacente est appelée toux chronique réfractaire (TCR). La toux persistante pour laquelle aucune cause sous-jacente n'est trouvée, est appelée toux chronique inexpliquée (TCI). Si le traitement de la maladie sous-jacente ne parvient pas à maîtriser la toux malgré une durée et une adhésion adéquates au traitement, les traitements par neuromodulateurs tels que l'orthophonie et/ou les opioïdes à faible dose, la gabapentine et la prégabaline peuvent être des options thérapeutiques. Il n'y a pas de traitement autorisé pour la TCR/TCI, mais une nouvelle classe de médicaments ciblant le récepteur purinergique P2X3 est actuellement à l'étude pour approbation réglementaire, avec d'autres antagonistes P2X3 en phase 2 et 3 de développement clinique. L'approbation de cette nouvelle classe de traitement peut représenter une avancée prometteuse pour les patients souffrant de toux chronique.